Horizontal Gene Transfer: From Evolutionary Flexibility to Disease Progression - Emamalipour, Melissa; Seidi, Khaled; Zununi Vahed, Sepideh; Jahanban-Esfahlan, Ali; Jaymand, Mehdi; Majdi, Hasan; Amoozgar, Zohreh; Chitkushev, L. T.; Javaheri, Tahereh; Jahanban-Esfahlan, Rana; Zare, Peyman (Frontiers in Cell and Developmental Biology, 2020)
Flexibility in the exchange of genetic material takes place between different organisms of the same or different species. This phenomenon is known to play a key role in the genetic, physiological and ecological performance of the host. Exchange of genetic materials can cause both beneficial and/or adverse biological consequences. Horizontal gene transfer (HGT) or lateral gene transfer (LGT) as a general mechanism leads to biodiversity and biological innovations in nature. HGT mediators are among the genetic engineering tools for selective introduction of desired changes in the genome for gene/cell therapy purposes. HGT, however, is crucial in development, emergence and recurrence of various human-related diseases, such as cancer, genetic-, metabolic-, and neurodegenerative disorders and can negatively affect the therapeutic outcome, by promoting resistant forms or disrupting the performance of genome editing toolkits. Because of the importance of HGT and its vital physio- and pathological roles, here the variety of HGT mechanisms is reviewed, ranging from extracellular vesicles (EVs) and nanotubes in prokaryotes to cell-free DNA and apoptotic bodies in eukaryotes. Next, we argue that HGT plays a role both in the development of useful features and in pathological states associated with emerging and recurrent forms of the disease. A better understanding of the different HGT mediators and their genome-altering effects/potentials may pave the way for the development of more effective therapeutic and diagnostic regimes.